Analisis Pengaruh Pengembangan Karir Dan Kompensasi Terhadap Kinerja Karyawan Pada PT. Supernova Flexible Packaging - Septi Sulianingsih; Rakhmat; Nurfai (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
The purpose of this research is to find out whether there is influence or how much influence career development and compensation variables have on employee performance at PT Supernova Flexible Packaging. The method used in this study is a quantitative method, data collection techniques used by distributing questionnaires and library data. The sample of this research is employees at PT Supernova Flexible Packaging, totaling 45 people with random sampling method. The analytical method used is multiple regression. The results of data processing using SPSS version 26 found linear regression results Y = 5.056 + 0.602X1 + 0.294X2. The results of SPSS data processing version 26 found that the adjusted R was 44.8%. This means that career development and compensation variables affect employee performance and the remaining 55.2% is influenced by other variables that are not used in this study. The results of this study concluded that partially career development and compensation variables have a positive effect on employee performance.. While simultaneously Career development and compensation together have a significant influence on employee performance in PT Supernova Flexible Packaging.